2004
DOI: 10.1161/01.hyp.0000132768.19056.33
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Sodium-Blood Pressure Plot “Stiffens”

Abstract: N early 50% of our population by 65 years of age has a systolic pressure within a "risky" range, that is, has predominantly systolic hypertension (PSH), 1 attributable, in part, to a reduction in large artery compliance because of an increased stiffness of the arterial wall. For a given pattern of left ventricular ejection, arterial stiffening reduces diastolic pressure and increases pulse pressure. Although increased arterial stiffness elevates pulse pressure, it is not itself sufficient to raise systolic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
(27 reference statements)
1
25
0
4
Order By: Relevance
“…166 Smooth muscle tone also increases because of endogenous Na pump ligands such as marinobufagenin or ouabain-like substances that increase with high-salt intake. 81 Among the pharmacological approaches for reducing vascular stiffness and/or its cardiac effects, diuretics, nitrates, and RAAS inhibitors are most commonly used. Although providing some usefulness, these agents have not solved the problem, and there remains a serious lack of effective therapies that directly target the structural abnormalities and changes in vascular signaling that underlie stiffening.…”
Section: May 2005mentioning
confidence: 99%
See 2 more Smart Citations
“…166 Smooth muscle tone also increases because of endogenous Na pump ligands such as marinobufagenin or ouabain-like substances that increase with high-salt intake. 81 Among the pharmacological approaches for reducing vascular stiffness and/or its cardiac effects, diuretics, nitrates, and RAAS inhibitors are most commonly used. Although providing some usefulness, these agents have not solved the problem, and there remains a serious lack of effective therapies that directly target the structural abnormalities and changes in vascular signaling that underlie stiffening.…”
Section: May 2005mentioning
confidence: 99%
“…79 Dietary salt augments vascular stiffness with increasing age, and low-sodium diets consumed by older adults improve arterial compliance. 80,81 In response to NaCl, VSMC tone is stimulated and vascular wall composition altered with a marked increase in the medial layer with VSMC hypertrophy and abundant collagen and elastin production. [82][83][84][85] Salt intake interacts with genetic polymorphisms for genes such as angiotensin type I receptors, nitric oxide, and ALDO synthase.…”
Section: Neuroendocrine Signaling and Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the adducin effects on organ damage may be due to renal Na retention that may promote organ damage, per se, as it occurs in a high-salt diet (5,7). A slight increase in body sodium may favor the production of reactive oxygen species (4,33,102,123), a well-known mediator of organ damage.…”
Section: Limits and Future Directionsmentioning
confidence: 99%
“…7 Although controversial, the preponderance of evidence now favors dietary salt-induced arterial stiffness in association with hypertrophy of the arterial wall, alteration of the vascular endothelial cells, and upregulation of angiotensin II receptors, all in the absence of a change in BP. 8 Similarly, there are abundant animal and human studies showing salt-dependent development of arterial stiffness and left ventricular hypertrophy that is independent of an increase in BP. 9 The recent study by Sesso et al 10 has clearly shown that elevated plasma C-reactive protein was associated with the future development of hypertension in a dose-dependent manor.…”
mentioning
confidence: 99%